2014
DOI: 10.1111/febs.12671
|View full text |Cite
|
Sign up to set email alerts
|

The phosphate of pyridoxal‐5′‐phosphate is an acid/base catalyst in the mechanism of Pseudomonas fluorescens kynureninase

Abstract: Kynureninase (l‐kynurenine hydrolase, http://www.chem.qmul.ac.uk/iubmb/enzyme/EC3/7/1/3.html) catalyzes the hydrolytic cleavage of l‐kynurenine to l‐alanine and anthranilic acid. The proposed mechanism of the retro‐Claisen reaction requires extensive acid/base catalysis. Previous crystal structures showed that Tyr226 in the Pseudomonas fluorescens enzyme (Tyr275 in the human enzyme) hydrogen bonds to the phosphate of the pyridoxal‐5′‐phosphate (PLP) cofactor. This Tyr residue is strictly conserved in all seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…45,46 The residual activity was hypothesized to be due to a water-mediated hydride shift in the absence of Y226. 44 These data support the proposed role of the PLP phosphate group as the general base that deprotonates Y226 in catalysis.…”
Section: Ppi and Pi In General Acid-general Base Catalysissupporting
confidence: 62%
See 1 more Smart Citation
“…45,46 The residual activity was hypothesized to be due to a water-mediated hydride shift in the absence of Y226. 44 These data support the proposed role of the PLP phosphate group as the general base that deprotonates Y226 in catalysis.…”
Section: Ppi and Pi In General Acid-general Base Catalysissupporting
confidence: 62%
“…44 The mutation resulted in a reduction of the k cat by about 2800-fold for the substrate L-kynurenine, from 16 s −1 for the wild-type enzyme to 5.8 × 10 −3 s −1 for Y226F kynureninase. The k cat / K m saw a 375-fold reduction from 2.0×10 5 M −1 s −1 for the wild-type enzyme to 530 M −1 s −1 for Y226F kynureninase.…”
Section: Ppi and Pi In General Acid-general Base Catalysismentioning
confidence: 99%
“…The KynU enzyme is a dimer of identical subunits whose chemistry has been of great interest for nearly a century. ,, It is also highly conserved across multiple kingdoms and has been implicated in a number of diseases of the central nervous system . We showed that compound 7 has a K i value of 140.4 μM against P .…”
Section: Discussionmentioning
confidence: 88%
“…The KynU enzyme is a dimer of identical subunits whose chemistry has been of great interest for nearly a century. 22,58,59 It is also highly conserved across multiple kingdoms and has been implicated in a number of diseases of the central nervous system. 60 We showed that compound 7 has a K i value of 140.4 μM against P. aeruginosa rKynU, which is of the same order of magnitude as was reported for S-phenyl-L-cysteine (700 μM) and an order of magnitude higher than S-phenyl-L-cysteine S,Sdioxide (3.9 μM), both reported by Dua et al 23 These compounds are structurally related to compound 7, in that compound 7 is the sulfoxide form of S-phenyl-L-cysteine, and Sphenyl-L-cysteine S,S-dioxide is the sulfone form.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The phosphate group of PLP was proposed to interact with the substrate L-serine hydroxyl group and contributed to the critical intermediate formation and stereospecific orientation of formed quinonoid or carbanionic intermediates (Beattie et al, 2013). The phosphate group was also suggested functioning as an acid/base catalyst to promote proton transfer to aid in external aldimine formation and accelerating gem-diol intermediate formation in kynureninase-mediated hydrolytic cleavage reaction (Phillips et al, 2014).…”
Section: New Insights Into Plp Chemistry In Catalysismentioning
confidence: 99%